Creme of the crop: The search for the most economy-benefitting biodiesel feedstock in the Philippines - Dela Cruz, Jessamin Jana E. (Animo Repository, 2008)
Biodiesel has had wide acclaim as of recent years due to its alleged benefits to the environment and to the economy through a reduction on both greenhouse gases and imported oil. In the Philippines, such recognition is embodied in the Biofuels Act of 2006, which currently mandates a B1 blend in all the local gas stations in the country. Unfortunately, the potential economic benefits of utilizing a particular feedstock for such mandatory production have not been quantified by any existing research. In this manner, with the use of economic theory, the paper sets working criteria by which the most economy-benefitting biodiesel feedstock in the Philippines could be identified. These comprise of yield efficiency, tailpipe emissions, employment generation, foreign exchange savings, value added, and productive linkages, giving consideration to the food versus miles issue as well. Analysis of data coming from government agencies, scholarly journals, and the input-output table would include descriptive statistics and comparative assessments. From the results taken, jatropha was found to be the most economy-benefiting feedstock, assuming food security was prioritized over output inducement. Since coconut would have been the choice feedstock if the priority was reversed, it was suggested that both be used in Philippine biodiesel production using intercropping methods. Thereafter, recommendations were made as to how the Biodiesel Act of 2006 could be modified accordingly.